RELEVANSI KESALEHAN IBU TERHADAP PERKEMBANGAN KEPRIBADIAN ANAK PERSPEKTIF AL-QURAN: Studi QS. Ali Imran: 35-36 - Sufrin Efendi Lubis; Riem Malini Pane (LPPM UMC, 2025)
This study aims to describe the relevance of a mother's piety in the family to the development of a child's personality. This study is a qualitative study with a literature type. Data were collected using documentation techniques and then analyzed using content analysis techniques. The results of the study show that there are four points as evidence of the extent of the relationship between the development of a child's personality and the mother's piety. First, children are a gift from Allah SWT, which is natural and parents, especially mothers, are obliged to maintain this natural. Second, fathers and mothers have the same obligations to children but with different proportions, fathers are more emphasized on fulfilling material needs; food and clothing, while mothers are tasked with controlling the child's psychological and emotional development. Third, mothers are the main actors who shape children's personalities, therefore mothers play a role as teachers who determine the direction of children's personality development. Fourth, a person's development is influenced by their environment and mothers are the figures who interact most intensely with children, the good and or bad of children is largely determined by the mother who accompanies them.